UPAYA MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN PANCASILA MELALUI PENGEMBANGAN BUKU SAKU DI SMA NEGERI 1 RANTAU SELATAN - Ritonga, Davit; Rahmawati, Ilham (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2025)
This classroom action research aims to improve student learning outcomes through literacy culture in Pancasila Education for tenth-grade students of class X-2 at SMA Negeri 1 Rantau Selatan by developing a pocketbook media. The research subjects consisted of 36 students (20 females, 16 males). The research was conducted in two cycles; each cycle included planning, action, observation, and reflection. The main instruments were a learning outcome test, observation sheets for teacher-student activities, and student response questionnaires. The results showed an increase in the average test score from 68.3 (pre-action) to 78.1 in the first cycle and 85.6 in the second cycle. The overall student learning completeness increased from 47% to 86%. The pocketbook proved to be practical, engaging, and effective in stimulating independent literacy activities that could improve student learning outcomes.